Optimization of Waqf Productive in Halal Tourism in Indonesia - Meirani, Nadia; Pratiwi, Rizka Estisia (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2024)
The potential for halal tourism in Indonesia is considered to continue to grow, supported by the increasing needs of the Muslim community, both men and women, who can now be considered as one unit. This also indicates an increase in recognition and acceptance of Islamic socio-cultural practices, both in Indonesia and globally, which shows that Muslims are starting to receive attention in developed countries. Of course, this development aims to produce a multiplier effect, one of which is strengthening the economy. Optimizing waqf funds for halal tourism can be a solution to stimulate the Indonesian economy. This research aims to determine the extent to which waqf funds can develop in Indonesia. The method used in this research is a qualitative method by carrying out FGDs with experts in the field of waqf initiated by Wacid. The research results show that the potential for waqf funds in Indonesia can still be developed, but this is only limited by the knowledge of the Indonesian population about waqf itself, so in-depth socialization is needed to support literacy about waqf in Indonesia.